2016
DOI: 10.21037/mhealth.2016.05.01
|View full text |Cite
|
Sign up to set email alerts
|

A recommended guideline for the development of mHealth Apps

Abstract: Background: Mobile Health or mHealth applications cope with medical or health issues supported by smartphones. Being a part of great importance in healthcare, mHealth apps are able to improve both the quality of medical services and the safety of the patients. It is regarded to be a new field with great prospect that attracts the interest of the stakeholders and the developers, above all. Of all the entities involved, developers have to face many challenges classified in four pillars: the regulation framework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…This will, in turn, lower costs and increase availability. Moreover, the intervention was developed by a multidisciplinary team, including neurologists with headache expertise, a neurophysiologist, and software engineers based on the guidelines for developing mHealth apps and guidelines for behavioral treatment trials . It used sensors that have previously been validated as appropriate for biofeedback and we involved the target group throughout the whole development process.…”
Section: Discussionmentioning
confidence: 99%
“…This will, in turn, lower costs and increase availability. Moreover, the intervention was developed by a multidisciplinary team, including neurologists with headache expertise, a neurophysiologist, and software engineers based on the guidelines for developing mHealth apps and guidelines for behavioral treatment trials . It used sensors that have previously been validated as appropriate for biofeedback and we involved the target group throughout the whole development process.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that apps utilize expertise from health professionals for monitoring and feedback as well as provide the user with a more personalized experience to increase adherence to health behaviors (13). In fact, a review of health apps suggested a lack of trustworthiness of apps could be ameliorated by having a behavior change expert aid in app development (19). The apps in the present study have several of these attributes.…”
Section: Introductionmentioning
confidence: 87%
“…Prior to conducting the analysis we chose an IS design lens that both encompasses identifying the range of human user roles, and also the design issues and methods used for developing and evaluating M-health artefacts: areas lacking in the previous M-health studies reviewed. This responds to the more recent calls for design collaboration and IS focus in M-health app development that are now becoming evident [9,35].…”
Section: Accepted Manuscriptmentioning
confidence: 95%